Digital Marketing, Competitive Advantage, Moderation of Financial Self-Efficacy: Implications for Marketing Performance of MSME Sector of Processed Patin Fish Products in Kampar Regency, Riau Province - Mashur Fadli (Riau International Conference on Economics, Business and Accounting, 2025)
This study aims to measure the influence of digital marketing, competitive advantage, and financial self-efficacy as moderating variables and their impact on marketing performance in the MSME sector of processed patin fish products in Koto Mesjid Village, XIII Koto Kampar District. This study uses a quantitative approach with primary data collection by distributing questionnaires to 50 business actors and data processing using Partial Least Square (PLS) statistical techniques. The results of this study confirm that digital marketing does not have a significant effect on marketing performance, competitive advantage has a significant effect on marketing performance, financial self-efficacy variables have a direct and significant effect on marketing performance, financial self-efficacy variables do not moderate the effect of digital marketing on marketing performance, financial self-efficacy variables do not moderate the effect of competitive advantage on marketing performance. Several other factors or variables still affect marketing performance variables both directly and through moderation